Technology for Achieving Learning Objectives Through a System-Activity Approach and the Development of Critical Thinking in Geography Studies - Abdimanapov , Bakhadurkhan; Kumarbekuly, Sanat; Gaisin, Ilgizar (Journal of Ecohumanism, 2025)
This article explores the integration of technology through a system-activity approach to enhance critical thinking and achieve learning objectives in geography education. The system-activity approach, grounded in constructivist learning theory, emphasizes active learning, student engagement, and critical thinking development. By incorporating digital tools such as Geographic Information Systems (GIS) and Virtual Reality (VR), the approach enables students to explore complex geographical phenomena, analyze spatial data, and engage with real-world problems interactively. This study employs survey methodology to assess the impact of technology-enhanced, activity-based learning on students’ critical thinking and overall learning outcomes. The findings underscore the effectiveness of the system-activity framework in improving geography education by fostering deeper engagement and understanding of geographical concepts. This paper contributes to the ongoing discourse on educational innovation, offering insights for educators aiming to integrate modern technologies into geography studies to enhance student competencies in navigating modern information spaces and developing essential 21st-century skills.